Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Round Table Terhadap Keterampilan Menulis Teks Prosedur Siswa Kelas XI SMA Negeri 2 Sutera - Upit Yulianti; Samsiarni; Refta Anjela (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
This study aims to describe the effect of using the round table cooperative learning model on the procedural text writing skills of class XI students of SMA Negeri 2 Sutera. This type of research is quantitative research using experimental methods. This study used a pre-experimental design. The population of this study were 25 class XI students of SMA Negeri 2 Sutera. The data in this study were scores on the results of the writing skills of procedure texts for class XI students of SMA Negeri 2 Sutera before and after using the round table cooperative learning model. The results of this study are first, the skills of writing text procedures for class XI students of SMA Negeri 2 Sutera before using the round table type cooperative learning model obtained an average value of 62.83 including Cuku qualifications in the 56-65% range. Second, the writing skills of the class XI students of SMA Negeri 2 Sutera after using the round table cooperative learning model obtained an average score of 87.83 including the Very Good qualification in the range of 86-95%. Third, there is a significant effect on the use of the round table type of cooperative learning model on the writing skills of procedure texts for class XI students of SMA Negeri 2 Sutera because t count> t table (16.45> 1.71).